Linking firms' green mode and process innovations: Central and Eastern European region case - Prokop, Viktor; Stejskal, Jan; Gerstlberger, Wolfgang; Zapletal, David; Nhan, Do Thi Thanh (Univerzita Tomáše Bati ve Zlíně, 2024)
This paper focuses on the hitherto less explored issue regarding the nature of the relationship between firms' green mode (including setting environmental targets, monitoring environmental burden, and adopting measures against environmental burden) and the production of process innovations. For these purposes, we focus on the countries of Central and Eastern Europe, which, together with their eastern neighbors, have historically represented the main polluters of the European environment. By using the World Bank Enterprise Survey and data from 3,299 firms in the Czech Republic, Estonia, Latvia, Lithuania, Poland, and Slovakia and the binary logistic regression, we provide evidence that a firm's green mode expressed, for example, by its monitoring of energy consumption or adoption of measures of environmental burden, can significantly trigger its introduction of process innovations. Moreover, we show that a firm's membership in firm groups increases its chances to introduce process innovations. In contrast, we show that firm age does not play a role in our analyses. Our results contribute to the innovation and sustainability literature, especially to the ongoing discussion regarding the innovation and environmental performance of Central and Eastern European countries. In addition, we note several practical implications of our research.
Propojení ekologického režimu a procesních inovací firem: případ regionu střední a východní Evropy
Keywords: Process innovation; environmental behavior; green mode; Central and Eastern Europe; Inovace procesů; environmentální chování; zelený režim; střední a východní Evropy